Comparative the impact intraoperative phrenic nerve sacrifice on prognosis patients with thymoma - Hongyun Ruan; Xuehui Shang; Dongjie Yan; Bin Liu; Fangchao Liu; Zhi Yang (BMC Pulmonary Medicine)
Abstract Objectives Complete removal of the tumor and surrounding tissue is the most important prognostic factor such as survival after surgery. When the tumor invades the phrenic nerve, the impact of intraoperative phrenic nerve sacrifice on the short- and long-term prognosis of patients is not clear. This study aims to explore the differences in prognosis between patients with malignant thymoma with and without phrenic nerve sacrifice during surgery, as well as analyze related factors. Methods A total of 209 patients who underwent thymoma resection in the Department of Thoracic Surgery at our hospital from February 2006 to November 2022 were collected for retrospective analysis. The groups were divided into two according to the presence or absence of intraoperative phrenic nerve sacrifice. A comparative analysis was conducted on postoperative complications, long-term survival recurrence between the two groups. Cox regression was used to analyze the factors related to the differences in short- and long-term prognosis between two groups. Results 29.6% of patients developed phrenic nerve sacrifice during thymoma surgery. Compared to patients without phrenic nerve sacrifice, the long-term survival rate was lower (P = 0.031). The independent risk factors for reduced long-term survival were intraoperative phrenic nerve sacrifice, secondary postoperative complications, and modified Masaoka staging III/IV. Conclusion Our data show that nearly one-third of patients develop phrenic nerve sacrifice during complete resection of thymoma. Phrenic nerve sacrifice has significant impact on short-term complications and long-term survival. Secondary postoperative complications and modified Masaoka staging III/IV are also risk factors for reduced long-term survival.